The light shift of a chip-scale atomic clock affected by asymmetrical multi-chromatic laser fields. Issue 4 (21st April 2017) - Yin, Yi; Tian, Yuan; Wang, Yuan-Chao; Gu, Si-Hong
ABSTRACT: As the light shift of a chip-scale atomic clock is influenced by asymmetrical power distributions from multi-chromatic laser fields, a mathematical formula was derived to calculate the light shift of coherent population trapping spectral line produced by such fields. The light shift was analyzed using this formula as well as measured experimentally. A comparison of the two established a basic agreement. The results revealed the relational characteristics between the light shift and the extent of asymmetry in the power distribution of the multi-chromatic laser fields. The optimal setup to suppress light shift in a chip-scale atomic clock was pointed out.